PENGEMBANGAN BAHAN AJAR BERBASIS ANDROID PADA MATERI SISTEM KOLOID MELALUI PENDEKATAN PROBLEM BASED LEARNING - Dewi Handayani; Nabilah Diomara; Rina Elvia (University of Bengkulu, 2022)
This study aims to determine the level of feasibility, level of readability, student response and level of student understanding after using android-based teaching materials on colloidal system materials through the Problem-based Learning approach. The model used in this development research is ADDIE which consists of the stages of analyze, design, development, implementation and evaluation. The research was conducted at SMA Negeri 2 Rejang Lebong with research subjects, namely 9 students of class XII MIPA 2 for small-scale trials and 35 students of class XII IPA 4 for large-scale trials. From the results of the study, it was found that (1) the feasibility level of android-based teaching materials on colloidal system materials through the Problem Based Learning approach was stated to be very valid and very legible. This is shown from the results of the validity test and readability test obtained, namely the percentage of validity of the material expert's assessment of 87.22 %, the percentage of validity of the assessment of media experts by 92.17 % and the percentage of readability of the assessment from students of 86.98 %, (2) student responses are stated to be very interesting, judging from the results of student responses obtained by 87.26%, (3) the level of student understanding after using android-based teaching materials through the Problem Based Learning approach is at a moderate level seen from the results of the N-Gain average score obtained from the pre-test and post-test values ​​of 0.65. The results of this study indicate that android-based teaching materials through the Problem Based Learning approach that have been developed are feasible to be used as teaching materials in realizing active learning and helping students understand colloidal system material. Keywords : teaching materials, android, colloid system, problem based learning